Quantification of taxanes in a leaf and twig extract from Taxus baccata L. using 13C NMR spectroscopy. (5th September 2013) - Paoli, Mathieu; Bighelli, Ange; Castola, Vincent; Tomi, Félix; Casanova, Joseph
Abstract : In the course of our ongoing work on the chemical characterization of Taxus baccata L. growing wild in Corsica, we have developed and validated a method for direct quantification of taxane derivatives by 13 C NMR using 10‐deacetylbaccatin III as reference compound and 1, 6‐hexanediol as internal standard. We have observed good accuracy (relative errors between 0.3% and 3.5%), linearity ( R 2 = 0.999) and precision (reproducibility 8.5 mg ± 1.1%) of the measurements. The experimental procedure was applied to the quantification of six identified taxanes in a fraction of chromatography of a methanol extract of T . baccata leaves. This method can be applied to other compounds bearing the taxane skeleton. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We have developed and validated a method for direct quantification of taxane derivatives by 13 C NMR using 10‐deacetylbaccatin III as reference compound and 1, 6‐hexanediol as internal standard. We have observed good accuracy, linearity and precision of the measurements. The experimental procedure was applied to the quantification of six identified taxanes in a fraction of chromatography of a methanol extract of Taxus baccata L. leaves. This method can be applied to other compounds bearing the taxane skeleton.